2013
DOI: 10.3111/13696998.2013.830974
|View full text |Cite
|
Sign up to set email alerts
|

Burden of menstrual symptoms in Japanese women: results from a survey-based study

Abstract: To the authors' knowledge, this is the first large-scale research assessing outcomes by severity categories for all menstrual symptoms and women's perception of bleeding. A large proportion of women suffer from menstrual symptoms, and symptom severity impacts women's lives. Menstrual symptoms lead to significant economic burden, mainly due to work productivity loss. However, the majority of women do not visit a gynecologist, even when their menstrual symptoms are severe. Thus, increasing public awareness on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 7 publications
2
89
1
Order By: Relevance
“…The age distribution in the current study was highly similar to other cross-sectional survey studies on dysmenorrhea in Japan 57,15. A larger proportion of participants in this study were employed (full time, part time, or self-employed) than in the two studies that reported on this variable,5,6 although the annual household income distribution in the current study was in line with a study by Tanaka et al5 Most participants in this study had normal BMI, whereas the majority of participants in a study by Nohara et al were underweight 7. Additionally, OTC analgesic use in this study was moderately higher than that of outpatients, as well as women in the general population, with dysmenorrhea in studies by Tanaka et al,5,6 yet much lower than the OTC analgesic use reported by women with dysmenorrhea who did not seek medical treatment 5.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The age distribution in the current study was highly similar to other cross-sectional survey studies on dysmenorrhea in Japan 57,15. A larger proportion of participants in this study were employed (full time, part time, or self-employed) than in the two studies that reported on this variable,5,6 although the annual household income distribution in the current study was in line with a study by Tanaka et al5 Most participants in this study had normal BMI, whereas the majority of participants in a study by Nohara et al were underweight 7. Additionally, OTC analgesic use in this study was moderately higher than that of outpatients, as well as women in the general population, with dysmenorrhea in studies by Tanaka et al,5,6 yet much lower than the OTC analgesic use reported by women with dysmenorrhea who did not seek medical treatment 5.…”
Section: Discussionsupporting
confidence: 82%
“…Respondents were also asked to self-report on the level of work productivity loss they experienced over the past 3 months and the past 6 months due to dysmenorrhea using a measure that was based on a prior study of dysmenorrhea in Japan 6. The specific items and response options were as follows: during the previous 3 (or 6) months, I was absent from work/school work/household chores due to dysmenorrhea symptoms (yes/no; if yes, respondent was asked to report the total number of days); during the previous 3 (or 6) months, I decreased work/school work/household chores volume or time due to dysmenorrhea symptoms (yes/no; if yes, respondent was asked to report the total number of days); during the previous 3 (or 6) months, there were days I had decreased efficiency in work/school work/household chores due to dysmenorrhea symptoms (yes/no; if yes, respondent was asked to report the total number of days).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Women with increased menstrual bleeding experience work loss 16 and are more likely to use health care, 17 resulting in a measurable economic burden. 18 The amount of iron lost per cycle in women with heavy bleeding averages 5e6 times more than in women with average blood loss and results in significant depletion of their iron stores. 19 Iron deficiency produces important clinical problems, including fatigue, atrophic epithelial changes, oral lesions, dysphagia, nail lesions, and reduced immune response.…”
mentioning
confidence: 99%